An Account of the Kingdom of Nepaul : Being the Substance of Observations Made During a Mission to that Country in the Year 1793 - Kirkpatrick, Colonel, (Brill | Manohar Publishers & Distributors, 2024)
An Account of the Kingdom of Nepaul is the description of the Kingdom of Nepal in the late eighteenth century. It covers the en route to Kathmandu and other regions in Nepalese country. It is a first-hand account offered by a British official posted in the region in 1793 when the Nepalese kingdom sought help from the British following the Chinese incursion in Kathmandu and the existing dispute with Tibet. This book offers Nepal's historical sketch, the economic systems, military organization, and judicial system followed during the reign of the Nepal kingdom. Kirkpatrick discusses the temple towns and village life, customs, and mannerisms of the Nepalese people. The book also covers the language, tribal communities, numismatics, and religion of the country.